Designing implementation strategies to improve identification, cascade testing, and management of families with familial hypercholesterolemia: An intervention mapping approach - Jones, Laney K.; Calvo, Evan M.; Campbell-Salome, Gemme; Walters, Nicole L.; Brangan, Andrew; Rodriguez, Gabriela; Ahmed, Catherine D.; Morgan, Kelly M.; Gidding, Samuel S.; Williams, Marc S.; Brownson, Ross C.; Seaton, Terry L.; et al. (Frontiers in Health Services, 2023)
Introduction. Familial hypercholesterolemia (FH) is a common inherited cholesterol disorder that, without early intervention, leads to premature cardiovascular disease. Multilevel strategies that target all components of FH care including identification, cascade testing, and management are needed to address gaps that exist in FH care. We utilized intervention mapping, a systematic, implementation science approach, to identify and match strategies to existing barriers and develop programs to improve FH care. Methods. Data were collected utilizing two methods: a scoping review of published literature related to any component of FH care, and a parallel mixed method study using interviews and surveys. The scientific literature was searched using key words including ‘barriers’ or ‘facilitators’ and ‘familial hypercholesterolemia’ from inception to December 1, 2021. The parallel mixed method study recruited individuals and families with FH to participate in either dyadic interviews (N=11 dyads/22 individuals) or online surveys (N=98 respondents). Data generated from the scoping review, dyadic interviews, and online surveys were used in the 6-step intervention mapping process. Steps 1-3 included a needs assessment, development of program outcomes and creation of evidence-based implementation strategies. Steps 4-6 included program development, implementation, and evaluation of implementation strategies. Results. In steps 1-3, a needs assessment found barriers to FH care included underdiagnosis of the condition which led to suboptimal management due to a myriad of determinants including knowledge gaps, negative attitudes, and risk misperceptions by individuals with FH and clinicians. Literature review highlighted barriers to FH care at the health system level, notably the relative lack of genetic testing resources and infrastructure needed to support FH diagnosis and treatment. Examples of strategies to overcome identified barriers included development of multidisciplinary care teams and educational programs. In steps 4-6, an NHLBI-funded study, the Collaborative Approach to Reach Everyone with FH (CARE-FH), deployed strategies that focused on improving identification of FH in primary care settings. The CARE-FH study is used as an example to describe program development, implementation, and evaluation techniques of implementation strategies. Conclusion. The development and deployment of evidence-based implementation strategies that address barriers to FH care are important next steps to improve identification, cascade testing, and management.